Mutagenic evaluation and chemical investigation of Byrsonima intermedia A. Juss. leaf extracts - Sannomiya, Miriam; Cardoso, Cassia R. P.; Figueiredo, Maria E.; Rodrigues, Clenilson M.; dos Santos, Lourdes C.; dos Santos, Fabio V.; Serpeloni, Juliana M.; Colus, Ilce M. S.; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP] (Elsevier B.V., 2007)
Byrsonima intermedia is a native species of the cerrado formation (tropical American savannah). In Brazil, this plant has been used for the treatment of fever, in ulcers, as a diuretic, as antiasthinatics and in skin infections. Members of the genus Byrsonima (Malpighiaceae) are employed not only in the folk medicine but also as food to make juice, jellies and liquor. The aim of this work was to evaluate the mutagenic effects of Byrsonima intermedia, common name 'murici'. Phytochernical analysis of methanol extract furnished (+)catechin, (-)-epicatechin, quercetin-3-O-beta-D-galactopyranoside, methyl gallate, gallic acid, quercetin-3-O-alpha-L-arabinopyranoside, amentoflavone, quercetin, querceti n-3-O-(2-O-galloyl)-beta-galactopyranoside and quei-eetin-3-O-(2-O-galloyl)-alpha-arabinopyranoside. Methanol, hydromethanol and chloroform extracts were evaluated in inutagenic assay with Salmonella typhimurium (Ames test) and mice (Micronucleus test). The methanolic extract presented signs of mutagenic activity for the strains TA98 and TA100 in the Ames assay. Mutagenicity was not observed in vivo. (c) 2007 Elsevier B.V.. All rights reserved.
Keywords: Byrsonima intermedia; Malpighiaceae; mutagenic activity; Ames test; micronuclei; mice